A Study of Regenerative Farming Practices and Sustainable Coffee of Ethnic Minorities Farmers in the Central Highlands of Vietnam - Le, Quan Vu; Cowal, Sanya; Jovanovic, Grace; Le, Don-Thuan (Frontiers in Sustainable Food Systems, 2021)
Coffee is highly vulnerable to climate change, thus impacting coffee-dependent livelihoods and economies. As rising temperatures continue to reduce the suitability of many historical coffee-growing regions, some farmers are practicing regenerative, organic coffee farming as a means of climate change mitigation. In the Central Highlands, the primary coffee growing region of Vietnam, conventional sun-grown, monocrop coffee requires intensive inputs, including fertilizers, pesticides and water. However, some farmers are converting their conventional sun farms to organic shade farms utilizing regenerative farming techniques for both environmental and economic reasons. This study examined regenerative farming practices and sustainable coffee in a small ethnic minority village in Lâm Ðồng province. The comparative analysis between soil samples taken from a regenerative shade-grown coffee farm and two conventional sun-grown coffee farms revealed that the soil of the regenerative farm, enriched with organic manure, is comparable to, or healthier than, the soil on the conventional farms enriched with chemical fertilizers. The results indicate that regenerative farming practices promote biodiversity; however, they also maintain microclimates that promote the growth of Roya fungus, which can decrease coffee yields. The economic analysis of farm costs and net returns found that regenerative farming practices decrease external inputs through a system of crop diversification and integrated livestock production that improves productivity and economic performance while preserving the ecological and environmental integrity of the landscape. Regenerative agriculture is an important step toward climate change adaptation and mitigation; however, in order for the farm communities in the Central Highlands to make the transition to regenerative agriculture, the success factors and benefits of this method must be demonstrated to the coffee farmers.